Effect of Profitability, Leverage, Liquidity and Activity Against Financial Distress Conditions - Sugiarto Sugiarto; Setyo Mahanani (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to determine the effect of profitability, leverage, liquidity and activity on financial distress. The research period is 2018. The approach in this study is quantitative research with all manufacturing companies listed on the IDX in 2018 as the population, which were then selected by purposive sampling method to obtain samples. This research uses logistic regression analysis method. The results of the study indicate that profitability has a negative effect on financial distress as indicated by the regression coefficient of -0.40732. and the prob value. 0.0097 is less than 0.05. Leverage has a positif effect on financial distress. This refers to the regression coefficient of 0.090522 and the prob value. 0.0353<0.05. Liquidity has no effect on financial distress conditions. This refers to the regression coefficient of 0.003604 and the resulting significance value is greater than the required level of significance, namely 0.503> 0.05. Activity has negative effect on financial distress. This refers to the regression coefficient of -0.09906 and the resulting significance value is less than required, namely 0.0047<0.05.